2017
DOI: 10.3390/rs10010001
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Wave Height Events in NW Spain: A Combined Multi-Sensor and Model Approach

Abstract: The Galician coast (NW Spain) is a region that is strongly influenced by the presence of low pressure systems in the mid-Atlantic Ocean and the periodic passage of storms that give rise to severe sea states. Since its wave climate is one of the most energetic in Europe, the objectives of this paper were twofold. The first objective was to characterize the most extreme wave height events in Galicia over the wintertime of a two-year period (2015-2016) by using reliable high-frequency radar wave parameters in con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Among the tools able to retrieve spatial data, HF radar is a remote sensing technique that has the capability of providing a relatively large coverage with high temporal and spatial resolution. Nowadays, this technology plays an essential role in monitoring surface currents ( [1][2][3]), whereas the suitability of its wave products for different applications has only recently begun to be explored ( [4][5][6][7]).…”
Section: Introductionmentioning
confidence: 99%
“…Among the tools able to retrieve spatial data, HF radar is a remote sensing technique that has the capability of providing a relatively large coverage with high temporal and spatial resolution. Nowadays, this technology plays an essential role in monitoring surface currents ( [1][2][3]), whereas the suitability of its wave products for different applications has only recently begun to be explored ( [4][5][6][7]).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the recent progress in HF radar measurement of wind-wave parameters (e.g., [4,5]), we should be able to evaluate the detection probability along the beams for a tsunami scenario in real time in the near future. In addition, we will soon apply the present method for longer-range NJRC HF radars with a center frequency of 13.5 MHz, to be deployed on the southeast coast of Kyushu Island in Miyazaki Prefecture (see Figure 1) and operated from April 2019.…”
Section: Discussionmentioning
confidence: 99%
“…2018, 10, 1126 2 of 17 periodic time oscillations in the wave parameters (height, period, direction) forced by semidiurnal tides, which was never observed before HF radar. Recently, Lorente et al [5] demonstrated the significant advantages of HF radar in surface wave measurements, with moderate root mean squared error and correlation coefficients, based on comparisons between HF radar and in situ wave observations during a winter season including extreme wave height events (significant wave height > 10 m). HF radar application for tsunami detection has been discussed theoretically and numerically over the past 40 years (e.g., [6,7]), and since the velocity fields of a tsunami were first measured using HF radar (e.g., [8][9][10]), the development of HF radar systems for tsunami detection has progressed.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, recent efforts have been focused on the improvement of wave height estimation for highly variable sea states by using dual-frequency HFR systems (Wyatt and Green, 2009). HFR-derived wave measurements also have a broad range of practical applications and can be used as benchmark for wave model skill assessment (Lorente et al, 2018), as input for assimilation into SWAN or Wavewatch III models (Waters et al, 2013), or for the analysis of extreme wave height events (Atan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%